The New Woman in Fiction and Fact
XVI, 258 p.
Keywords: A cultural icon of the fin de siècle , the New Woman was not one figure, but several. In the guise of a bicycling, cigarette-smoking Amazon, the New Woman romped through the pages of Punch and popular fiction; as a neurasthenic victim of social oppression, she suffered in the pages of New Woman novels such as Sarah Grand's hugely successful The Heavenly Twins . The New Woman in Fiction and Fact marks a radically new departure in nineteenth-century scholarship to explore the polyvocal nature of the late Victorian debates around gender, motherhood, class, race and imperialism which converged in the name of the New Woman.